FEATURES OF FAMILY COMMUNICATION IN EDUCATION - Bahronova, Komila Yadgorovna (Educational Research in Universal Sciences, 2023)
The article details the problems that arise in adolescence, as well as aspects of raising adolescents in the family. In recent years, in our republic, in order to democratize and humanize all spheres of society, the education system has been given the task of forming a healthy, active, responsible and independent person, and the necessary legal framework has been created. “Psychological monitoring of the personal, mental and social development of students of different age periods, the identification of psychological defects in education, the prevention of any negative deviations, ... the organization and implementation of measures for correction, social rehabilitation gives a positive result.” In this sense, this can become a sufficient basis for the scientific study of the socio-psychological factors that cause changes in children of primary school age.